Rediscovery, redescription, and reclassification of the rare and unusual fly Pyrgometopa penicillata Kertész (Diptera: Drosophilidae) - Pirani, Gabriela; Grimaldi, David A. (Zootaxa, 2019)
For slightly more than a century only the type specimen has been known for Pyrgometopa penicillata, a monotypic genus of Drosophilidae whose sole species has an ocellar triangle distended into a bizarre tubercle bearing a tuft of large, spine-like bristles in both sexes. Here we report additional specimens of both sexes of the species, recently rediscovered from Brazil, Peru and French Guyana, allowing us to state that Pyrgometopa is a junior synonym for Stegana, a large cosmopolitan genus. A detailed redescription of Stegana penicillata (Kertész) new combination is provided, including new morphological information, like the male and female terminalia, the egg and a short discussion is provided about its hallmark feature.